2017
DOI: 10.1111/cyt.12450
|View full text |Cite
|
Sign up to set email alerts
|

Modification of The Paris System for urinary tract washing specimens using diagnostic cytological features

Abstract: TPS is a useful diagnostic system for urinary tract washing specimens by decreasing the number of AUC cases and increasing sensitivity. In this study, anisonucleosis and India ink nuclei improved the diagnostic accuracy of HGUC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…The reported effect on sensitivity for diagnosing HGUC has also varied among studies, with some studies reporting an increase in sensitivity and others reporting a decrease in sensitivity . At our institution, the baseline sensitivity, at >80%, is higher than that of the pre‐TPS classification in most other studies, which report 60% to 70% sensitivity for HGUC . In the current study, after careful reclassification of atypical cases to TPS categories, in total, 3 cases were reclassified as NHGUC but demonstrated HGUC on surgical biopsy.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…The reported effect on sensitivity for diagnosing HGUC has also varied among studies, with some studies reporting an increase in sensitivity and others reporting a decrease in sensitivity . At our institution, the baseline sensitivity, at >80%, is higher than that of the pre‐TPS classification in most other studies, which report 60% to 70% sensitivity for HGUC . In the current study, after careful reclassification of atypical cases to TPS categories, in total, 3 cases were reclassified as NHGUC but demonstrated HGUC on surgical biopsy.…”
Section: Discussionmentioning
confidence: 49%
“…The current findings demonstrated that TPS and TPS‐like methods improve the performance of urine cytology by lowering the rate of the atypical diagnosis while significantly increasing the PPV of the atypical diagnosis for HGUC. Several recent studies also have reported similar findings . A single study reported an increase in atypical diagnoses (from 3% to 24% in benign cases) and a lowering of specificity; however, that study consisted primarily of voided specimens, which can have more degenerative artifacts that mimic HGUC .…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…How does the experience of the authors compare with that of other institutions? Not unexpectedly, using a set of standardized criteria resulted in a reduction of the rates of atypical urothelial cells (AUC) from their pre‐Paris values of 6.60% to 41.20% (a 34.6% range) to 5.30% to 26.00% (a 20.7% range) after the implementation of TPS . Most institutions experienced decreases in AUC rates; the sole outlier was an institution with very low pre‐Paris AUC rates …”
mentioning
confidence: 99%